Quantification of extracellular vesicles in vitro and in vivo using sensitive bioluminescence imaging. Issue 1 (21st August 2020) - Gupta, Dhanu; Liang, Xiuming; Pavlova, Svetlana; Wiklander, Oscar P.B; Corso, Giulia; Zhao, Ying; Saher, Osama; Bost, Jeremy; Zickler, Antje M.; Piffko, Andras; Maire, Cecile L.; Ricklefs, Franz L.; et al.
ABSTRACT: Extracellular vesicles (EVs) are naturally occurring nano‐sized carriers that are secreted by cells and facilitate cell‐to‐cell communication by their unique ability to transfer biologically active cargo. Despite the pronounced increase in our understanding of EVs over the last decade, from disease pathophysiology to therapeutic drug delivery, improved molecular tools to track their therapeutic delivery are still needed. Unfortunately, the present catalogue of tools utilised for EV labelling lacks sensitivity or are not sufficiently specific. Here, we have explored the bioluminescent labelling of EVs using different luciferase enzymes tethered to CD63 to achieve a highly sensitive system for in vitro and in vivo tracking of EVs. Using tetraspanin fusions to either NanoLuc or ThermoLuc permits performing highly sensitive in vivo quantification of EVs or real‐time imaging, respectively, at low cost and in a semi‐high throughput manner. We find that the in vivo distribution pattern of EVs is determined by the route of injection, but that different EV subpopulations display differences in biodistribution patterns. By applying this technology for real‐time non‐invasive in vivo imaging of EVs, we show that their distribution to different internal organs occurs just minutes after administration.